2016
DOI: 10.7863/ultra.15.11023
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Elastosonography of the Myotendinous Junction: Normal Behavior and Correlation With a Standard Measurement System During Functional Tests

Abstract: Objectives-In recent years, an increasing need to use imaging to assess normal and adaptive muscle function, in addition to its anatomy and structure, has emerged. We evaluated the myotendinous junction's elastosonographic behavior in light of the most recent literature on its physiologic behavior. The elastosonographic studies were compared with the results obtained from a standard measurement system to ensure a correlation with maximal muscle contraction.Methods-Nineteen male professional soccer players were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…This finding is also supported by the elastogram color map, that showed predominantly soft and edematous appearance plantar fasciopathy, whereas in the asymptomatic contralateral healthy side showed higher elasticity color-coding map. These findings are indicative of the presence of less rigid, edematous tissue in patients with plantar fasciopathy in accordance with data in the literature [15,34,36]. SWEv well describes the plantar fascia structural alteration due to fasciopathy, indeed showing lower values in plantar fasciopathy than the healthy asymptomatic plantar fascia [37].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is also supported by the elastogram color map, that showed predominantly soft and edematous appearance plantar fasciopathy, whereas in the asymptomatic contralateral healthy side showed higher elasticity color-coding map. These findings are indicative of the presence of less rigid, edematous tissue in patients with plantar fasciopathy in accordance with data in the literature [15,34,36]. SWEv well describes the plantar fascia structural alteration due to fasciopathy, indeed showing lower values in plantar fasciopathy than the healthy asymptomatic plantar fascia [37].…”
Section: Discussionsupporting
confidence: 90%
“…Elastography is a recently developed, non-invasive ultrasonographic imaging technique that provides information on tissue elasticity and stiffness [11][12][13][14][15]. There are two main elastographic techniques widely used: strain elastography (SE) and shear wave elastography (SWE) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed a stiffness increase during contraction: in particular, doubling of the SWE value from the rest position to concentric contraction during the calf rise test. These findings were in accordance with our previous study, in which we found higher baseline elasticity and a higher overall decrease in elasticity during a contraction in the healthy rectus femoris MTJ. Changes in stiffness during contraction reflect the physiologic characteristics of muscle and tendon interaction; indeed, it is known that the ability of muscle to absorb and generate mechanical work is related to interactions between the contractile components of the muscle and elastic structures associated with its tendons and aponeuroses .…”
Section: Discussionsupporting
confidence: 94%
“…[16][17][18][19][20] Shear wave elastography (SWE), a recently developed, noninvasive ultrasound (US) imaging technique, has been used to assess the mechanical properties of muscles and tendons. [21][22][23][24][25][26][27][28] It provides information on tissue elasticity and stiffness by using an impulse generated by the transducer with the shear wave propagating at a higher speed in stiffer tissues 29 and seems to be able to detect modifications of tissue elasticity earlier than conventional B-mode US. 30,31 The aim of our study was to evaluate the characteristics of the medial gastrocnemius MTJ with SWE in a resting position and during muscle contraction in healthy people.…”
mentioning
confidence: 99%
“…Actually US elastography has been established as an excellent diagnostic method for evaluating the biomechanical properties in liver fibrosis, breast cancer, and thyroid cancer. Furthermore, in the musculoskeletal field, many research studies have been conducted on sonoelastography since the early 1990s but only recently it has been applied to clinical practice [20][21][22]. The use of SWE to study muscles has increased exponentially in the last few years, in particular research studies have been conducted in the evaluation of myopathy, chronic stroke and also of cerebral palsy patients [23][24][25].…”
Section: Discussionmentioning
confidence: 99%